Effect of a regenerator on hybrid solar gas turbine performance in Barranquilla, Colombia (2021)
A thermodynamic analysis of a hybrid gas turbine solar plant, represented in three basic subsystems related to the power cycle, the combustion chamber subsystem, and the solar concentrator subsystem, allows evaluating the performance of a hybrid cycle from a reduced number of parameters, which include energy losses in each of its components. The solar radiation values are estimated with an evaluated and validated theoretical model, the combustion chamber uses natural gas as fuel and the numerical values of the system are taken from the Solugas experimental plant in Spain. This work presents an integrated model that allows to estimate the operation of a hybrid solar Brayton power plant in any place and day of the year. The evaluation of the plant in Barranquilla, Colombia is shown from the influence of the regenerator has on the plant performance and solar concentrating system. The results show that the regenerator can increase the overall efficiency of the plant by 29% and allows reaching a maximum temperature of the central receiver of the concentrator of 1044 K at noon, when solar radiation is maximum.